Symptoms, but Not a Biomarker Response to Inhaled Corticosteroids, Predict Asthma in Preschool Children with Recurrent Wheeze - E. M. M. Klaassen; K. D. G. van de Kant; Q. Jöbsis; S. T. P. Høvig; C. P. van Schayck; G. T. Rijkers; E. Dompeling (Mediators of Inflammation)
Background. A reliable asthma diagnosis is challenging in preschool wheezing children. As inhaled corticosteroids (ICS) are more effective in asthmatics than in children with transient wheeze, an ICS response might be helpful in early asthma diagnosis. Methods. 175 children (aged two–four years) with recurrent wheeze received 200 μg Beclomethasone extra-fine daily for eight weeks. Changes in Exhaled Breath Condensate (EBC) biomarkers (pH, interleukin (IL)-1α, IL-2, IL-4, IL-5, IL-10, IFN-γ, sICAM, and CCL-11), Fractional exhaled Nitric Oxide (FeNO), airway resistance, and symptoms were assessed. At six years of age a child was diagnosed as transient wheezer or asthmatic. Adjusted logistic regression analysis was performed with multiple testing correction. Results. 106 transient wheezers and 64 asthmatics were analysed at six years of age. Neither changes in EBC biomarkers, nor FeNO, airway resistance, or symptoms during ICS trial at preschool age were related to asthma diagnosis at six years of age. However, asthmatics had more airway symptoms before the start of the ICS trial than transient wheezers (P<0.01). Discussion. Although symptom score in preschool wheezing children at baseline was associated with asthma at six years of age, EBC biomarkers, airway resistance, or symptom response to ICS at preschool age could not predict asthma diagnosis at six years of age.